Dyslipidemia is insufficiently treated in antiphospholipid syndrome patients. (October 2022) - Yelnik, Cécile M; Martin, Claire; Ledoult, Emmanuel; Sanges, Sébastien; Sobanski, Vincent; Farhat, Meryem; Morell-Dubois, Sandrine; Maillard, Hélène; Drumez, Elodie; Launay, David; Hachulla, Eric; Lambert, Marc
Objectives: Although dyslipidemia is a strong risk factor for thrombosis in antiphospholipid syndrome (APS), it has been poorly studied. This study aimed to assess lipids profile and risk factors for unachieved cholesterol levels in a real-life APS population. Methods: Inclusion criteria were: APS diagnosis according to international classification criteria, referring to the out-patients clinic of our tertiary care center for their follow-up, and having a blood sample collection for lipids levels determination. Cholesterol level targets for each patient were defined according to 2019 ESC/EAS guidelines for the management of dyslipidemia. Results: Between January 2020 and April 2021, 114 APS patients were included (male 37 (32.5%); mean age 49 ± 14 years). Among them, 40 (35.1%) had a history of dyslipidemia, 48 (42.1%) were under lipid-lowering therapies, and 59 (51.8%) had a history of cardiovascular disease (CVD). Mean levels of low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), and triglyceride were, respectively, 110 ± 40 mg/dL, 60±20 mg/dL, and 120 (80–190) mg/dL. Unachieved LDL-C levels were found in 77 (67.5%) patients of whom 53 had history of CVD. Overall, 90 (78.9%) had protective HDL-C and 31 (27.2%) had hypertriglyceridemia. In the multivariate analysis, independent risk factors for unachieved LDL-C levels were older age and history of CVD; triple aPL negativity, defined as complete disappearance of aPL over time in APS patients who were previously positive in accordance to international criteria, was an independent protective factor for unachieved LDL-C. Conclusion: Our finding suggested that dyslipidemia is frequent in APS patients and mainly insufficiently treated, especially in patients with history of CVD, who are at highest risk of future CV events.